Medicine, Law and Public Policy in Scotland : c. 1850-1990. - Crowther, M. A. (Edinburgh University Press, 2011)
Marks the contribution of Anne Crowther to scholarship in British history. Focusing on Scotland, this collection draws together the three main strands of€her academic research welfare, medicine and legal history and reflects the range of her.